Clustering and assessing carbon peak statuses of typical cities in underdeveloped Western China. (1st January 2023) - Lin, Huaxing; Zhou, Ziqian; Chen, Shun; Jiang, Ping
Graphical abstract: Highlights: Focus is put on city-level carbon peak statuses in less-developed areas of China. Data used in the study are collected from 76 cities in western China from 2005 to 2020. The cluster analysis and carbon peak trends are made for selected western cities in China. A more relaxed carbon peak policy and sufficient emission space are necessary for sample cities. Abstract: As the main source of carbon emissions, cities are vital for achieving China's carbon peak goal by 2030. However, few studies have focused on China's city-level carbon emissions peak, particularly in the underdeveloped western region of China. Therefore, this study explores the peak carbon statuses and trends of cities in less-developed western China. We applied a self-organising map neural network to perform cluster analysis within 76 cities, combined with the decoupling coefficient method and Mann-Kendall test to evaluate the peak carbon trend of cities. The results showed that cities in western China can be divided into resource-dependent cities, low-carbon buffer cities, economic priority cities, and low-carbon transition cities. We also discussed the unbalanced and asynchronous characteristics of paths to achieve carbon peaks in these cities, which should be addressed in China's strategy of achieving carbon peaks.